The effect of coaching on the simulated malingering of memory impairment - Brett Alexandra (BMC Neurology, 2008)
Abstract Background Detecting malingering or exaggeration of impairments in brain function after traumatic brain injury is of increasing importance in neuropsychological assessment. Lawyers involved in brain injury litigation cases routinely coach their clients how to approach neuropsychological testing to their advantage. Thus, it is important to know how robust assessment methods are with respect to symptom malingering or exaggeration. Methods The influence of different coaching methods on the simulated malingering of memory impairments is investigated in neurologically healthy participants using the Short-Term-Memory Test from the Bremer Symptom-Validierung (STM-BSV). Cut-offs were derived from patients with mild to severe traumatic brain injury. For comparison purposes, the German adaptation of the Rey Auditory Verbal Learning Test (AVLT), and the Rey 15 Items Test (FIT) were additionally administered. Four groups of neurologically healthy subjects were instructed to (1) perform as best as they can, (2) simulate brain injury, (3) simulate brain injury and received additional information about the sequelae of head trauma, (4) simulate brain injury and received additional information on how to avoid detection. Furthermore, a group of patients with mild to severe closed head injury performed the tests with best effort. Results The naïve simulator and the symptom coached groups were the easiest to detect, whereas the symptom plus test coached group was the hardest to detect. The AVLT and the FIT were not suited to detect simulators (sensitivities from 0% to 50.8% at 75% specificity) whereas the STM-BSV detected simulators with 67% – 88% sensitivity at a specificity of 73%. However, the STM-BSV was not robust to coaching. Conclusion The present investigation shows that symptom validity testing as implemented in the BSV-STM is one clinically useful element in the detection of memory malingering. However, clinicians have to be aware that coaching influences performance in the test.